Conversion of the interleukin 1 receptor antagonist into an agonist by site-specific mutagenesis. - Ju, G (1991)
Interleukin 1 (IL-1) receptor antagonist (IL-1ra) is a naturally occurring protein that binds to the IL-1 receptor present on T cells, fibroblasts, and other cell types and acts to block IL-1-induced responses. IL-1ra is a pure antagonist and has no agonist activity in in vitro or in vivo systems. By site-specific mutagenesis, an analog of IL-1ra was created that contained a substitution of a single amino acid, Lys-145----Asp. This analog, IL-1ra K145D, exhibited partial agonist activity in the D10.G4.1 cell proliferation assay. The newly acquired agonist activity could not be neutralized by antisera to IL-1 alpha or IL-1 beta, but it could be blocked by a monoclonal antibody to the T-cell IL-1 receptor. The analog also showed agonist activity as assayed by increased prostaglandin E2 synthesis from CHO cells expressing recombinant mouse IL-1 receptor. These results with IL-1ra K145D demonstrate the importance of the region surrounding the corresponding Asp-145 residue in IL-1 beta for triggering the biological response to IL-1.